If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + 2) = 3(y + -7) Reorder the terms: 2(2 + y) = 3(y + -7) (2 * 2 + y * 2) = 3(y + -7) (4 + 2y) = 3(y + -7) Reorder the terms: 4 + 2y = 3(-7 + y) 4 + 2y = (-7 * 3 + y * 3) 4 + 2y = (-21 + 3y) Solving 4 + 2y = -21 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 4 + 2y + -3y = -21 + 3y + -3y Combine like terms: 2y + -3y = -1y 4 + -1y = -21 + 3y + -3y Combine like terms: 3y + -3y = 0 4 + -1y = -21 + 0 4 + -1y = -21 Add '-4' to each side of the equation. 4 + -4 + -1y = -21 + -4 Combine like terms: 4 + -4 = 0 0 + -1y = -21 + -4 -1y = -21 + -4 Combine like terms: -21 + -4 = -25 -1y = -25 Divide each side by '-1'. y = 25 Simplifying y = 25
| 3x+3-2x=10 | | 425=4x+25y | | (-2x+8)-(x^2+x-7)= | | -0.5=(-2)/4 | | 6x-3x+x-8+4x= | | 25x+8-28x=1-8 | | (x-5)(x-10)=0 | | 76y=25(3y+17) | | 2-2=9x+4x | | 7-12x-4x^2=0 | | y-4=8y | | 4=8-x/3 | | -19-(-16)+(-5)-19= | | -0.5=x/4 | | 22y=7(3y-4) | | 4x+3y-3=-15 | | 5y+2-2y=4y+-1 | | 14y=13(y+4) | | -6=3(-2) | | 5(x-5)=110/11 | | 10y^2-2y+3=0 | | 5m+7+4(3m-5)=5(m+5) | | -2-9=5x+6-4x | | 4x+6-3=12 | | x+17=38 | | -2x-2x=19-7 | | 11+3(3y+5)= | | n/2=-4 | | -10y=-90 | | 2x-21=-.8 | | 2x-21=-8 | | 11n=10n+23 |